Autonomous Underwater Vehicles (AUVs) for Deep-Sea Exploration and Environmental Monitoring - Danang Danang; Everett Quinn Adler; Dawson Zane (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The advancement of Autonomous Underwater Vehicles (AUVs) is transforming the way scientists conduct deep-sea exploration and environmental monitoring. AUVs equipped with sophisticated sonar, AI-driven navigation systems, and real-time data transmission capabilities can explore extreme marine environments where human intervention is impossible. This paper reviews state-of-the-art developments in AUV technology, including enhanced battery efficiency, swarm intelligence for coordinated underwater missions, and AI-based anomaly detection for marine biodiversity assessment. Additionally, the study highlights the role of AUVs in disaster response, such as oil spill detection and ocean pollution analysis. By addressing technical challenges such as communication latency, data processing in harsh environments, and energy efficiency, this research aims to contribute to the next generation of AUV applications.